2020
DOI: 10.1371/journal.ppat.1009120
|View full text |Cite
|
Sign up to set email alerts
|

Key interplay between the co-opted sorting nexin-BAR proteins and PI3P phosphoinositide in the formation of the tombusvirus replicase

Abstract: Positive-strand RNA viruses replicate in host cells by forming large viral replication organelles, which harbor numerous membrane-bound viral replicase complexes (VRCs). In spite of its essential role in viral replication, the biogenesis of the VRCs is not fully understood. The authors identified critical roles of cellular membrane-shaping proteins and PI(3)P (phosphatidylinositol 3-phosphate) phosphoinositide, a minor lipid with key functions in endosomal vesicle trafficking and autophagosome biogenesis, in V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 76 publications
0
15
0
Order By: Relevance
“…Asuka et al have previously reported co-localization of fluorescently-labeled EBOV particles with SNX5 in the process of researching the internalization mechanism of EBOV [ 252 ]. In addition, SNX5 and PI (3) P play a key role in the formation of the viral replicase complexes (VRCs) bound on the organelle membrane of the tomato bushy stunt virus (TBSV) [ 253 ]. Importantly, HCMV-encoded UL35 binds to and negatively regulates SNX5, thereby regulating cellular transport pathways that affect the virus assembly process [ 254 ].…”
Section: Virus-specific Induction Of Autophagymentioning
confidence: 99%
“…Asuka et al have previously reported co-localization of fluorescently-labeled EBOV particles with SNX5 in the process of researching the internalization mechanism of EBOV [ 252 ]. In addition, SNX5 and PI (3) P play a key role in the formation of the viral replicase complexes (VRCs) bound on the organelle membrane of the tomato bushy stunt virus (TBSV) [ 253 ]. Importantly, HCMV-encoded UL35 binds to and negatively regulates SNX5, thereby regulating cellular transport pathways that affect the virus assembly process [ 254 ].…”
Section: Virus-specific Induction Of Autophagymentioning
confidence: 99%
“…VRO formation requires subversion of several membranous compartments and vesicles as well as numerous co-opted cytosolic host proteins [2,3,[5][6][7][8][71][72][73][74]. Indeed, tombusviruses co-opt cellular membranous carriers, such as retromer-based tubular carriers, COPII vesicles and their selected cargoes via p33-based targeting of cellular membrane proteins, such as Rab1 and Rab5 small GTPases or the retromer complex and delivering them to the VROs for various functions and membrane modifications and membrane proliferation [51,52,[75][76][77]. Another major function of p33 is the selection of the TBSV (+)RNA for replication and recruitment into VROs [32,78].…”
Section: Discussionmentioning
confidence: 99%
“…The functions of these host factors range from having direct roles in altering membrane structures to indirect roles in forming the specific membrane or lipid environments required for virus-driven processes. For instance, the membrane shaping functions of ESCRT proteins and BAR domain containing proteins are involved for TBSV vROs biogenesis [7][8][9]. TBSV-induced peroxisome:ER membrane contact sites contain several lipid metabolism or transfer proteins that facilitate movement of lipid species between these membrane domains, likely providing lipids required for replication.…”
Section: Structure and Biogenesis: Insights From Model Virusesmentioning
confidence: 99%